DIGITAL NOMADISM IN BULGARIA: RETHINKING SOCIAL IDENTITY ANDCULTURAL BOUNDARIES IN THE GLOBAL ERA - Petrova, Yoana; Petrov, Daniel (E-Journal VFU, 2024)
In the digital age, characterized by technological innovations andglobalization, digital nomadism rethinks the traditional notions of identity and belonging. Thestudy examines the influence of modern infrastructure, economic accessibility, andintercultural communication on both professional and personal development. Interviews withrepresentatives from various sectors underscore that this phenomenon integrates the localwith the global, forming new social networks and hybrid identities that respond to thechallenges of today's social context.
Keywords: digital nomadism; identity; globalization; intercultural exchange; digital infrastructure